Beyond sensitivity: what are the enabling opportunities of OPM-MEG? - Timothy P. L. Roberts; Timothy P. L. Roberts; Charlotte Birnbaum; Luke Bloy; William Gaetz; William Gaetz (Frontiers in Medical Technology)
While optically-pumped magnetometer (OPM) technology offers a number of compelling advantages over its SQUID predecessor for magnetoencephalography (MEG), many studies and viewpoints focus on issues of (i) scalp placement, with commensurate increases in sensitivity to weak magnetic fields and (ii) room temperature operation (without the need for baths of liquid helium to maintain superconducting properties of SQUIDs). This article addresses another unique and tantalizing opportunity—the ability for the OPM array to be “wearable”, and thus to move with the participant. This is critical in adoption of naturalistic paradigms that move beyond “laboratory neuroscience” toward “real world neuroscience”. It is also critically important in application to pediatric populations who cannot or will not remain still during conventional MEG scan procedures. Application to the developing infant brain will be considered as well as application to pediatric neuropsychiatric and developmental disorders, such as autism spectrum disorder. Rather than present solutions, this article will highlight the challenges faced by conventional SQUID-based cryo-MEG and explore the potential avenues for OPM-MEG to make a positive impact to the field of pediatric neuroscience.